Regional brain stiffness changes across the Alzheimer's disease spectrum - Matthew C. Murphy; David T. Jones; Clifford R. Jack Jr.; Kevin J. Glaser; Matthew L. Senjem; Armando Manduca; Joel P. Felmlee; Rickey E. Carter; Richard L. Ehman; John Huston III (NeuroImage: Clinical, 2016)
Magnetic resonance elastography (MRE) is an MRI-based technique to noninvasively measure tissue stiffness. Currently well established for clinical use in the liver, MRE is increasingly being investigated to measure brain stiffness as a novel biomarker of a variety of neurological diseases. The purpose of this work was to apply a recently developed MRE pipeline to measure regional brain stiffness changes in human subjects across the Alzheimer's disease (AD) spectrum, and to gain insights into the biological processes underlying those stiffness changes by correlating stiffness with existing biomarkers of AD. The results indicate that stiffness changes occur mostly in the frontal, parietal and temporal lobes, in accordance with the known topography of AD pathology. Furthermore, stiffness in those areas correlates with existing imaging biomarkers of AD including hippocampal volumes and amyloid PET. Additional analysis revealed preliminary but significant evidence that the relationship between brain stiffness and AD severity is nonlinear and non-monotonic. Given that similar relationships have been observed in functional MRI experiments, we used task-free fMRI data to test the hypothesis that brain stiffness was sensitive to structural changes associated with altered functional connectivity. The analysis revealed that brain stiffness is significantly and positively correlated with default mode network connectivity. Therefore, brain stiffness as measured by MRE has potential to provide new and essential insights into the temporal dynamics of AD, as well as the relationship between functional and structural plasticity as it relates to AD pathophysiology.